Teamwork during the COVID-19 Pandemic - Daniel Lajčin; Dáša Porubčanová (Emerging Science Journal, 2021)
The essential of presented paper is human resource management, especially the concept of teamwork in home office conditions, for which both the state and the private sector of the Czech Republic were not used before the declaring a state emergency to prevent the spread of COVID-19. The presented paper has a classical structuring of the scientific paper, it is divided into a theoretical part and an empirical part. The theoretical part of the paper is based on a critical analysis of relevant information sources, which we have chosen with regard to the topic of the paper and the timeliness of the information provided in the information source. To synthesize and generalize the outputs of the critical analysis of information sources, we used a procedure from general to specific. In the empirical part of the presented paper we apply the information obtained to teams from the private sector and teams from the public sector. Using a questionnaire survey, we compare these two groups of teams in the areas of the concept of teamwork, team functionality, team management by its leader and motivation to perform in the context of the preparedness of the analyzed teams for home office. We found that greater negativity of teamwork as less productivity, or more demanding communication, is perceived by people from a private sector. Increased work from home in the private sector has improved communication and, in the public sector, work efficiency. In public sector, there is more frequent work control and feedback. Doi: 10.28991/esj-2021-SPER-01 Full Text: PDF